2013
DOI: 10.2319/113012-911.1
|View full text |Cite
|
Sign up to set email alerts
|

Release of metal ions from fixed orthodontic appliance: An in vitro study in continuous flow system

Abstract: Objective: To evaluate the release of metal ions from fixed orthodontic appliances. Materials and Methods: A new system for in vitro testing of dental materials was constructed and consisted of a thermostatic glass reactor that enabled immersion of the studied material. Experimental conditions reflected the human oral cavity, with a temperature of 37uC and a saliva flow rate of 0.5 mL/min. The simulated fixed orthodontic appliance made of stainless steel was evaluated. Sampling was performed at several time po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 21 publications
3
35
1
3
Order By: Relevance
“…Concentration analysis of metals after the placement of the appliance showed that copper remains in the mouth longer (24 hours) than cadmium (10 minutes) 5 . In addition, cadmium is found in the formulation of alginate (irreversible hydrocolloid) with the aim of improving its physical, chemical and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Concentration analysis of metals after the placement of the appliance showed that copper remains in the mouth longer (24 hours) than cadmium (10 minutes) 5 . In addition, cadmium is found in the formulation of alginate (irreversible hydrocolloid) with the aim of improving its physical, chemical and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The results of cell viability for the Gemini ® were lower in the 16-day immersion, illustrating that a high concentration of metal ions was released at the beginning of the experiment, after the possibility of a passive layer [2]. The SEM showed that there were no differences between the topographies of the brackets before and after treatment.…”
Section: Discussionmentioning
confidence: 80%
“…Mikulewicz et al, the result of this study also showed that the highest concentration of ion released was at the beginning of the experiment. It was found passivation probably occurred from stainless steel and it found that the ion released is not toxic to humans [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations